Artificial Intelligence: Methodology, Systems, and Applications 15th International Conference, AIMSA 2012, Varna, Bulgaria, September 12-15, 2012, Proceedings - Ramsay, Allan; Agre, Gennady (Lecture Notes in Artificial Intelligence, 2012)
This book constitutes the refereed proceedings of the 15th International Conference on Artificial Intelligence: Methodology, Systems, and Applications, AIMSA 2012, held in Varna, Bulgaria in September 2012. The 36 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on natural language processing, social networks, knowledge representation and reasoning, machine learning, planning and agents, search, and computer vision.